2021
DOI: 10.1007/s13762-021-03372-5
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of ibuprofen by photo-based advanced oxidation processes: exploring methods of activation and related reaction routes

Abstract: Several homogeneous photo-based advanced oxidation processes-namely photolysis, photo-oxidation, and photo-Fenton oxidation-were investigated for the elimination of ibuprofen in water. The effects of several operating parameters, such as the lamp type (low or medium pressure mercury, xenon-arc), the concentration of hydrogen peroxide (0.5 to 7 times the stoichiometric amount required for mineralization), and the concentration of Fenton reagent, were quantified. Photo-Fenton oxidation was also combined with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 81 publications
2
6
0
Order By: Relevance
“…It was determined that all PPCPs degraded according to pseudo‐first‐order kinetics in the Fenton process. [ 59 ] Similar to this study, studies have generally shown that CBZ, [ 60 ] DFC, [ 61 ] IBU, [ 62 ] PRC, [ 63 ] and TRC [ 64 ] exhibit pseudo‐first‐order kinetics of photodegradation. The degradation rates for UV/H 2 O 2 and UV/TiO 2 processes demonstrated a proportional increase with the quantity of H 2 O 2 , and TiO 2 added to the solution.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…It was determined that all PPCPs degraded according to pseudo‐first‐order kinetics in the Fenton process. [ 59 ] Similar to this study, studies have generally shown that CBZ, [ 60 ] DFC, [ 61 ] IBU, [ 62 ] PRC, [ 63 ] and TRC [ 64 ] exhibit pseudo‐first‐order kinetics of photodegradation. The degradation rates for UV/H 2 O 2 and UV/TiO 2 processes demonstrated a proportional increase with the quantity of H 2 O 2 , and TiO 2 added to the solution.…”
Section: Resultssupporting
confidence: 77%
“…It was determined that all PPCPs degraded according to pseudofirst-order kinetics in the Fenton process. [59] Similar to this study, studies have generally shown that CBZ, [60] DFC, [61] IBU, [62] PRC, [63] and TRC [64] exhibit pseudo-first-order kinetics of photodegradation.…”
Section: Kinetic Studiessupporting
confidence: 86%
“…Moreover, to cope with the ever-increasing needs of the world's population, an enormous intensification has transpired in the industrial and agricultural sectors, escalating the gravity of the situation. 1 These sectors are not only consuming gigantic amounts of water resources but are also greatly affecting the quality of the aquifers. 2 Water pollution is a serious challenge due to the release of a variety of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…These processes typically rely on the generation of highly reactive hydroxyl radicals (OH), which in turn attack the organics, resulting in being extremely effective for their abatement [14]. There are various types of AOPs that can be successfully applied for the liquid waste treatment, such as Fenton, Fenton-like, ozonation, as well as electrochemical and photochemical technologies [15][16][17][18][19][20][21][22][23]; however, their effectiveness depends upon their ability to generate oxidizing species. The conventional Fenton process is the most widely used AOP because of its simplicity and economic feasibility, but there are several drawbacks associated with this process.…”
Section: Introductionmentioning
confidence: 99%